Magnetic Levitational Assembly for Living Material Fabrication. Issue 10 (14th April 2015) - Tasoglu, Savas; Yu, Chu Hsiang; Liaudanskaya, Volha; Guven, Sinan; Migliaresi, Claudio; Demirci, Utkan
<x xml:space="preserve">Abstract</x> Functional living materials with microscale compositional topographies are prevalent in nature. However, the creation of biomaterials composed of living micro building blocks, each programmed by composition, functionality, and shape, is still a challenge. A powerful yet simple approach to create living materials using a levitation‐based magnetic method is presented.